2021
DOI: 10.3389/fmicb.2021.715701
|View full text |Cite
|
Sign up to set email alerts
|

Combined Untargeted and Targeted Metabolomics Approaches Reveal Urinary Changes of Amino Acids and Energy Metabolism in Canine Babesiosis With Different Levels of Kidney Function

Abstract: Canine babesiosis is a tick-borne disease with a worldwide distribution, caused by the haemoprotozoan parasites of the genus Babesia. One of the most prevalent complication is acute kidney injury, and an early diagnosis of altered kidney function remains a challenge for veterinary practice. The aim of this study was to assess the urine metabolic profile from dogs with babesiosis and different degree of kidney function using untargeted and targeted MS-based metabolomics approaches. In this study, 22 dogs natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…Other signi cantly affected pathways were related to lipid metabolism, and included proteins such as apolipoproteins (apoA-I, apoA-IV, apoB, apoE, apoM, apoH) and plasma retinol-binding protein (RBP4). A link between babesiosis and lipid metabolism in the host has already been documented by transcriptomics, proteomics, and metabolomics studies 20,44,45 . The importance of lipid metabolism in babesiosis is suggested to be related to the catabolic reaction during the acute phase response in the host.…”
Section: Proteomic Pro Ling Between Control Group Uncomplicated and C...mentioning
confidence: 85%
“…Other signi cantly affected pathways were related to lipid metabolism, and included proteins such as apolipoproteins (apoA-I, apoA-IV, apoB, apoE, apoM, apoH) and plasma retinol-binding protein (RBP4). A link between babesiosis and lipid metabolism in the host has already been documented by transcriptomics, proteomics, and metabolomics studies 20,44,45 . The importance of lipid metabolism in babesiosis is suggested to be related to the catabolic reaction during the acute phase response in the host.…”
Section: Proteomic Pro Ling Between Control Group Uncomplicated and C...mentioning
confidence: 85%
“…There are only a few existing studies of the metabolome of Babesia. Previous investigations assessed differences in the metabolism of free merozoites and infected RBCs (iRBCs) during B. divergens infection and in the urine metabolic profiles of dogs with B. canis infection using metabolomics approaches (Fernańdez-Garcia et al, 2021;Kulešet al, 2021;Beri et al, 2023). Recent research on metabolic profiling was based on erythrocytes separated from B. microti-infected mice and found sabotage of metabolic pathways in iRBCs, including amino acid, lipid, and nucleotide metabolism and the tricarboxylic acid cycle (Gong et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…field [27]. Our previous study assessed the urine metabolic profile in dogs with babesiosis using untargeted and targeted MS-based metabolomics approaches, and demonstrated that kidney dysfunction accompanying canine babesiosis was associated with changes in amino acid metabolism, energy metabolism, and fatty acid metabolism [28].…”
Section: The Metabolomics Dataset In Dogs Infected With B Canismentioning
confidence: 99%